Online learning resources and social media platforms used by medical students during the COVID-19 pandemic - Samy A. Azer; Deema Alhudaithi; Fay AlBuqami; Haifa AlWaily; Razan AlRabah; Raghad AlKhashan (BMC Medical Education, 2023)
Abstract Background The unprecedented COVID-19 pandemic has caused significant disruption to medical students’ education. It imposed challenges that required rapid adaptation to enforced lockdowns and remote learning and changed curriculum delivery from in-person to online learning and virtual technology. Objective This study aimed to determine the trends and ratings of using Internet resources and social media platforms by medical students during the COVID-19 pandemic. Methods A validated questionnaire was used to explore preferences for Internet resources and social media platforms among undergraduate medical students (years 1, 3, and 5) at King Saud University. The questionnaire comprised three sections- (i) demographic information, (ii) access and use of Internet resources/social media platforms, and (iii) students’ ratings and reasons for using technology-enabled learning during the COVID-19 pandemic. Results A total of 320 undergraduate medical students responded to the online questionnaire. The difference in the number of students using the Internet daily across academic years increased significantly as they progressed in the medical course (p = 0.025). For learning, YouTube and Videoconferencing (e.g. Zoom) were used by 83.1% and 73.4% of students, respectively, followed by WhatsApp 198 (61.9%). For social interaction, WhatsApp, 310 (96.6%); YouTube, 296 (92.8%); Twitter, 288 (90%); and Zoom, 269 (84.1%) were the platforms used by most students. Regarding concerns about the impact of COVID-19 and social isolation, 250 (78.1%) agreed that technology helped them gain a sense of connectedness to their peers. Over half of students, 187 (58.4%) wished that technologies be integrated more often in their courses, as 245 (76.7%) agreed that it helped engage them with classes. Conclusion The study shows that the use of the Internet and social media resources is increasing at all levels to fill the gap in learning and social interaction because of the COVID-19 pandemic. Medical institutions should embrace the effective use of Internet resources and use the experience gained and lessons learned in guiding educators on what type of online resources should be created to add value to students learning even post-pandemic.